The Impact of Policy Quantification on Rural Spatial Development in Suburbs: A Case Study of Dalian’s Main Urban Area - Jiaxiang Wang; Zehao Cao; Tian Chen; Chunguang Hu (Land)
Under China’s rural revitalization strategy, peri-urban villages function as pivotal nodes in urban–rural integration. Existing policy research predominantly emphasizes macro-level land and industrial policies, neglecting their spatial development effects on peri-urban villages. This study addresses the gap by constructing a policy quantification framework and employing a Vector Autoregression (VAR) model to analyze policy impacts on rural spatial development, focusing on peri-urban villages in Dalian’s main districts from 2004 to 2023. The results indicate a fluctuating yet upward trend in policy effectiveness. Initial supply-side policies prioritized infrastructure development, whereas subsequent demand-side policies significantly enhanced living conditions, underscoring the necessity of adaptive policy strategies. The rural revitalization construction index exhibited notable spatial heterogeneity, evolving from clusters near industrial zones to expansion into areas like the Jinzhou District, aligned with urban growth patterns. Granger causality analysis confirmed the strong influence of policy interventions, with the first-order lag VAR model offering reliable predictions of short- and long-term policy effects. Initially, the construction index was entirely self-driven (100%), but its reliance on self-influence waned to 69.8% over time, highlighting a transition toward greater policy-driven development.